Piperidine Nucleus as a Promising Scaffold for Alzheimer’s Disease: Current Landscape and Future Perspective - Grover, Parul; Rohilla, Suman; Bhardwaj, Monika; Mehta, Lovekesh; Malhotra, Anjleena (Current Topics in Medicinal Chemistry, 2023)
Heterocycles and their derivatives hold an important place in medicinal chemistry due to their vast therapeutic and pharmacological significance and wider implications in drug design and development. Piperidine is a nitrogen-containing heterocyclic moiety that exhibits an array of pharmacological properties. This review discusses the potential of piperidine derivatives against the neurodegenerative disease Alzheimer’s. The incidences of Alzheimer’s disease are increasing nowadays, and constant efforts are being made to develop a medicinal agent for this disease. We have highlighted the advancement in developing piperidine-based anti-neuronal disease compounds and the profound activities of some major piperidine-bearing drug molecules with their important target site. This review focuses on advancements in the field of natural and synthetic occurring piperidines active against Alzheimer’s disease, with emphasis on the past 6 years. The discussion also includes the structure-activity relationship, the structures of the most promising molecules, and their biological activities against Alzheimer’s disease. The promising activities revealed by these piperidinebased scaffolds undoubtedly place them at the forefront of discovering prospective drug candidates. Thus, it would be of great interest to researchers working on synthesizing neuroprotective drug candidates.
Keywords: Heterocycles